Special physical training for senior school pupils within the framework of the ‘Sports Games’ section - Solodovnik, E.M. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to determine attitudes towards basketball and volleyball as compulsory subjects and the actual level of mastery of basic technical elements in accordance with the Federal State Educational Standards. Methods and structure of the study. A questionnaire survey and pedagogical testing in basketball and volleyball were conducted among 25 first-year students. The article presents a study of the level of technical preparedness and attitude towards sports games among 9th grade graduates of schools in the Republic of Karelia. The work was carried out at the Petrozavodsk Basic Medical College. Results and conclusions. The results showed an extremely low level of training in basketball and insufficient training in volleyball (48% failed to master the underhand pass and serving accuracy). Forty per cent experienced negative feelings from basketball classes, 36% did not like the sport; the attitude towards volleyball was predominantly positive. Eight per cent noted that basketball was not taught at school at all, 12% did not remember such lessons. The author concludes that there has been a systematic deterioration in the quality of teaching since the abolition of the compulsory school sports competition (2012), a lack of supervision of physical education teachers and their low motivation, despite the high accessibility of the Lokobasket and KES-Basket projects. It is recommended to strengthen administrative control and restore the popularity of school sports games, as well as to increase the proportion of game sports in physical education classes.